The Influence of Job Stress on Employee Performance Mediated by Job Satisfaction: A Study on Employees in the Food & Beverage Industry in Jabodetabek, Indonesia - Gracia, Michella; Lusiana, Dewi (Manunggal Halim Jaya, 2025)
This study aims to analyze the effect of job stress on team member performance mediated by job satisfaction in food and beverage industry employees in Jabodetabek. Job stress, which is defined as a condition in which employees face job demands that exceed their capacity, can hurt individual performance. On the other hand, job satisfaction plays an important role in improving team member performance, where satisfied employees tend to show higher productivity. This study examines the relationship between these three variables to provide deeper insights into how organizations can manage stress and improve job satisfaction to boost employee performance. The research was conducted using a quantitative approach and purposive sampling technique using questionnaires distributed to 260 permanent employees of the food and beverage industry in Jabodetabek with at least 1 year of service. Data analysis was conducted using the PLS-SEM (Partial Least Square Structural Equation Modeling) method using SmartPLS 4 software. The results showed that job stress does not have a significant adverse effect on job satisfaction, job stress does not have a significant adverse effect on employee performance, job satisfaction has a significant positive effect on employee performance, and job stress has a significant positive effect on employee performance through job satisfaction.